Hybrid Internationalization in Korea: A Promising Development? - Lee, Hee Kyung; Rhee, Byung Shik (International Higher Education, 2018)
This article presents and analyzes a newly developed model of inbound internationalization of higher education in Korea—a demand-based, locally oriented, hybrid model of internationalization. This model combines existing features of internationalization—the typical study-abroad model in which international students are taught in the host country’s primary language and the decade-long Korean internationalization model, in which international students are educated in separate academic programs—with recently developed, demand-based educational programs. While conventional, English-language-driven internationalization strategies such as increasing the number of English as a medium of instruction (EMI) courses still exist, this hybrid model is becoming popular among Korean higher education institutions. Yet, although this model may seem better than conventional strategies, it still does not solve a main challenge of internationalization, academic capitalism—and it even reproduces it. This article is meant to help higher education institutions in developing countries whose primary language is not English to develop new internationalization strategies.